2010
DOI: 10.1002/jcla.20412
|View full text |Cite
|
Sign up to set email alerts
|

The activity of class I, II, III, and IV alcohol dehyrogenase isoenzymes and aldehyde dehydrogenase in endometrial cancer

Abstract: The increased activity of total ADH in endometrial cancer, especially the class I isoenzyme and normal activity of ALDH, may be the cause of disorders in metabolic pathways that use these isoenzymes and could increase the concentration of acetaldehyde, which is cancerogenic substance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Both the serum and tissue expression level of class I and total ADH were significantly increased in liver,27,28 colorectal,29,30 and brain cancers,31,32 while ALDH levels were not statistically significant different between cancer patients and healthy subjects. The upregulation trend of class I ADH between cancer and healthy tissue can also be found in cervical,33 ovarian,34 endometrial,35 and renal cell cancers,36 whereas the upregulation trend of class I ADH for cancer serum has been reported in bladder and esophageal cancers 37,38. However, the expression of class I ADH in breast cancer was significantly decreased compared to the tissue of healthy subjects, and the expression of ALDH was unchanged 39.…”
Section: Discussionmentioning
confidence: 94%
“…Both the serum and tissue expression level of class I and total ADH were significantly increased in liver,27,28 colorectal,29,30 and brain cancers,31,32 while ALDH levels were not statistically significant different between cancer patients and healthy subjects. The upregulation trend of class I ADH between cancer and healthy tissue can also be found in cervical,33 ovarian,34 endometrial,35 and renal cell cancers,36 whereas the upregulation trend of class I ADH for cancer serum has been reported in bladder and esophageal cancers 37,38. However, the expression of class I ADH in breast cancer was significantly decreased compared to the tissue of healthy subjects, and the expression of ALDH was unchanged 39.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, as in the serum results of patients with malignant neoplasms, ADH isoenzyme activity has been identified in tumor tissues ( 37 ). Studies have additionally reported that class I ADH isoenzymes are significantly increased in the tumor tissue of cervical cancer ( 47 ), ovarian cancer ( 48 ), endometrial cancer ( 49 ), brain cancer ( 50 ), liver cancer ( 44 , 51 ), CRC ( 52 , 53 ) and renal cell carcinoma ( 54 ) compared with healthy tissue, whereas ALDH isoenzymes in these cancer types did not demonstrate a statistically significant difference between cancer and healthy tissue. However, a downregulation of class I ADH was observed in breast cancer tissues ( 55 ), whereas the expression of other ADH isoenzymes remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…The study of ADH activity in women with uterus cancer are consistent with ovarian cancer results. In endometrial cancer and cervical cancer cells was found higher activity of ADH I and the total ADH without any changes in ALDH activity [6,7]. The study in women with breast cancer has shown an inverse association.…”
Section: Discussionmentioning
confidence: 83%
“…Acetaldehyde is the first metabolite of alcohol oxidation, mediated by alcohol dehydrogenase (ADH). Recent data shows that healthy and also cancerous cells of endometrium and cervix contain ADH class I, III and IV isoenzymes [6,7].…”
Section: Introductionmentioning
confidence: 99%